Indi'n Humor : Bicultural Play in Native America. - Lincoln, Kenneth (Oxford University Press, 1993)
Drawing upon history, psychology, folklore, linguistics, anthropology, and the arts, this book challenges "wooden Indian" stereotypes to redefine negative attitudes and humorless approaches to Native American peoples. Moving from tribal culture to interethnic literature, Lincoln covers thetraditional Trickster of origin myths, historical ironies, Euroamericans "playing Indian," feminist Indian humor at home, contemporary painters and playwrights reinventing Coyote, popular mixed-blood music and Red English, and three Native American novelists, Louise Erdrich, James Welch, and N. Scott Momaday.